2012
DOI: 10.1088/0957-4484/23/46/465703
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-enhanced Raman imaging of TiO2nanoparticles

Abstract: The interaction of anatase titanium dioxide (TiO(2)) nanoparticles with chemical vapour deposited graphene sheets transferred on glass substrates is investigated by using atomic force microscopy, Raman spectroscopy and imaging. Significant electronic interactions between the nanoparticles of TiO(2) and graphene were found. The changes in the graphene Raman peak positions and intensity ratios indicate that charge transfer between graphene and TiO(2) nanoparticles occurred, increasing the Raman signal of the TiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 32 publications
5
37
0
Order By: Relevance
“…The Raman spectrum of GO shows well referred documented D band peak at 1353 cm −1 , due to the sp 3 defects and an another peak of G band at 1597 cm −1 , which can be ascribed to the inplane vibrations of sp 2 carbon atoms and a doubly-degenerated phonon mode (E 2g symmetry) at the Brillouin zone centre15. It was also demonstrated that the D band peak remains unchanged while the G band peak of rGO was downshifted from 1597 cm −1 to 1587 cm −1 , owing to the “self-healing” characteristics of the rGO that recovers the hexagonal network of carbon atoms with defects16.…”
Section: Resultsmentioning
confidence: 80%
“…The Raman spectrum of GO shows well referred documented D band peak at 1353 cm −1 , due to the sp 3 defects and an another peak of G band at 1597 cm −1 , which can be ascribed to the inplane vibrations of sp 2 carbon atoms and a doubly-degenerated phonon mode (E 2g symmetry) at the Brillouin zone centre15. It was also demonstrated that the D band peak remains unchanged while the G band peak of rGO was downshifted from 1597 cm −1 to 1587 cm −1 , owing to the “self-healing” characteristics of the rGO that recovers the hexagonal network of carbon atoms with defects16.…”
Section: Resultsmentioning
confidence: 80%
“…After deposition of rGO layers on TiO 2 MLNTs, the additional two peaks D-band and G-band were observed for A/R-rGO MLNTs, besides the TiO 2 peaks. 19,21,22 The D-band at 1328 cm -1 was attributed to disordered sp 2 bonded carbon atoms or defects and the G-band at 1596 cm -1 was attributed to ordered sp 2 bonded carbon network (graphitic structure, E 2g mode), 23,24 confirms deposition of rGO layers on TiO 2 MLNTs. ) of anatase multi-leg nanotubes in which we observe branching of single nanotube into two tubes.…”
Section: Resultsmentioning
confidence: 95%
“…The surface-enhanced Raman scattering (SERS) has been extensively investigated [18-20]. The charge transfer between the two contacted materials is the chemical mechanism of Raman enhancement [21,22].…”
Section: Resultsmentioning
confidence: 99%